(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Medicinal plants have played a crucial role in traditional healing practices and continue to be a valuable source for modern pharmaceuticals. This review explores the ethnobotanical significance, phytochemical composition, and pharmacological properties of a selected medicinal plant. Ethnobotanical studies provide insights into the traditional uses of the plant in various cultures for treating a range of ailments, highlighting its long-standing importance in natural medicine. Phytochemical analysis reveals the presence of numerous bioactive compounds, including alkaloids, flavonoids, terpenes, and glycosides, which contribute to the plant’s therapeutic effects. These compounds have been linked to various pharmacological activities, such as anti-inflammatory, antioxidant, antimicrobial, and neuroprotective effects, which are supported by modern pharmacological research.